External Linkages and Policy Constraints in Saudi Arabia - Westelius, Niklas (IMF Working Papers; Working Paper, 2013)
The constraints that external linkages impose on domestic policy choices in Saudi Arabia have continuously evolved over the past four decades. This paper argues that two major ongoing developments in particular have affected and will continue to affect policy trade-offs. First, growing oil needs of emerging market economies (EMEs), and specifically those of developing Asia, have strengthened economic links between the Far East and Saudi Arabia. Second, financial sector development in Saudi Arabia has gradually strengthened the monetary transmission mechanism. The former implies the increased importance of developing Asia's growth cycle for the Saudi economy, while the latter suggests greater influence of U.S. monetary policy on the non-oil economy through the peg to the U.S dollar. As a result, divergence between the growth cycles in developing Asia and the United States has the potential to increasingly generate tension between policy objectives in Saudi Arabia.